Pengaruh Massa Dan Ukuran Partikel Adsorben Sabut Kelapa Terhadap Efisiensi Penyisihan Fe Pada Air Gambut - Istighfarini, Sri Ayu Emy; Daud, Syarfi; Hs, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water is surface water are blackish brown and metals Fe which requires effective and efficient processing to be worthy for use by the public. Various types of adsorbents continue to be developed, one of which is the coconut fiber adsorbent. The purpose of this study was to determine metal removal efficiency of Fe in the peat water, calculating the adsorption capacity and determine the appropriate type of isotherm. Fixed variables used in this study is the stirring speed of 150 rpm and a contact time of 60 minutes. For independent variables used consisted of adsorbent mass variation of 0.5, 1, 1.5, 2 g and a particle size variation 100, 140 and 200 mesh. Removal efficiency of Fe metal concentrations higher 84.67% by mass of adsorbent 2 g with a particle size of 200 mesh. Metal adsorption capacity of Fe achieved the highest on the mass of 0.5 grams with a particle size of 200 mesh amounted to 0.09596 mg Fe / g. Types of adsorption isotherms corresponding to Fe by coconut fiber adsorbents is Freundlich isotherm with R2 values of 0.9783 for Fe.Keywords : Adsorption, Adsorbent, Peat Water, Coconut Fiber.